The Mediating Role of Product Innovation on MSME Performance in Jakarta's Dairy Sector - Helda Jaya Puspita; Rini Hardiyani (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Dairy MSMEs play an important role in satisfying domestic milk demand, but they confront hurdles in consistently improving company performance. Product innovation is seen as a critical factor that can enhance the impact of MO and EO on MSME performance. The objective of this investigation is to investigate the impact of MO and EO on MSME performance, using product innovation as a mediating variable. The investigation took place in August and September 2024 at Pondok Ranggon, Jakarta, with 41 dairy farming SMEs selected using a saturated sampling technique. The key variables are market orientation (X1), entrepreneurial orientation (X2), product innovation (Y), and SME performance (Z). The data were analysed using SPSS version 30.0, which included multiple linear regression and path analysis. MO has a significant impact on product innovation (p < 0.05), whereas EO does not (p > 0.05). Product innovation has a significant impact on MSME performance (p < 0.05), but does not moderate the effect of MO or EO.